ARGUMENTATION IN CONTEMPORARY PERSUASIVE DISCOURSE - Kalemaj, Silvana (European Scientific Journal, ESJ, 2014)
The theory of argumentation is based on the assumption thatarguments pervade and partly regulate all verbal exchanges. Thus, the idea isthat, to speak is like to act upon an addressee by modifying his representationof the surrounding world. Through carefully planned discourse, speakerschoose specific words to represent their views and opinions and convert theiraudience toward their preferred line of action. In principle, argumentation isused to handle the difference of opinion in a way that results in theacceptance of the arguer‘s standpoint by the addressee. This rhetoricalprocedure is especially applied in public persuasive discourse.The study of argumentation in the context of persuasive speech hasboth a linguistic and social value since it emphasizes the role ofargumentation to transmit concepts and ideas for understanding thepersuasive communication of today which seems to serve particular interests.In classical times persuasive argumentation was heightened to an art formand used for the common good. The paper will address issues related withargument and argumentation theories, the use of language andargumentation in persuasive discourse, the notion of strategic maneuveringintroduced in the pragma-dialectical theory which refers to the continualefforts made in all moves that are carried out in argumentative discourse tokeep the balance between reasonableness and effectiveness.It will particularly examine the use of argumentation as an instrumentthat aims to persuade by means of reasoning and effectiveness. The actorsinvolved in argumentative discourse are primarily interested in resolving thedifference of opinion effectively in favor of their case that serves theirrhetorical interests best.The paper will also deal with rhetorical tactics in fallaciousargumentation and the strategies of illusionist argumentation, where logicalreasoning can seem to be an argument, but in effect is an emotional maskthat serves as a persuasive technique. To evaluate the types, the nature andpower of arguments, examples and case studies will be examined from the political and media field since argumentation is a prominent element ofspeech used in these domains.